2021
DOI: 10.3390/brainsci11091220
|View full text |Cite|
|
Sign up to set email alerts
|

Cognitive Function during the Prodromal Stage of Alzheimer’s Disease in Down Syndrome: Comparing Models

Abstract: Accurate identification of the prodromal stage of Alzheimer’s disease (AD), known as mild cognitive impairment (MCI), in adults with Down syndrome (MCI-DS) has been challenging because there are no established diagnostic criteria that can be applied for people with lifelong intellectual disabilities (ID). As such, the sequence of cognitive decline in adults with DS has been difficult to ascertain, and it is possible that domain constructs characterizing cognitive function in neurotypical adults do not generali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…In larger, more general cognitive test batteries used in DS cohorts at high‐risk for dementia, it was shown that while there is clear evidence that AMCI can be identified at the cognitive domain level, statistical methodology and inclusion/exclusion of covariates can lead to differing results. 35 Similarly to the CAMCOG‐DS, 25 tailoring and validation of the NAID for the DS population specifically ensures sensitivity to the AMCI‐DS clinical phenotype. 36 …”
Section: Discussionmentioning
confidence: 99%
“…In larger, more general cognitive test batteries used in DS cohorts at high‐risk for dementia, it was shown that while there is clear evidence that AMCI can be identified at the cognitive domain level, statistical methodology and inclusion/exclusion of covariates can lead to differing results. 35 Similarly to the CAMCOG‐DS, 25 tailoring and validation of the NAID for the DS population specifically ensures sensitivity to the AMCI‐DS clinical phenotype. 36 …”
Section: Discussionmentioning
confidence: 99%
“…To date, only a handful of large-sized studies have compared the trajectory of AD by premorbid ID level in DS [4,23,24]. These studies were limited in that they only stratified by mild versus moderate ID (excluded those with severe/profound ID), examined differences on only one or two cognitive measures, and analyses did not control for type of trisomy (full, mosaic, or translation) or apolipoprotein E (APOE) status (e.g., allele 4), genetic status, each which may have its own effect on the time course of AD clinical signs.…”
Section: Introductionmentioning
confidence: 99%
“…Two articles in this Special Issue, by Hom et al and Harp et al, examine the effectiveness of multiple measures of cognitive and behavioral functioning and the domains assessed in identifying dementia classification. The research by Hom et al [ 10 ] shows that cognitive functioning can be characterized at the cognitive domain level, with language, executive functioning and memory being candidates for most impacted domains. Building on this concept, Harp et al [ 11 ] developed an abbreviated test battery to identify individuals with DS at risk for AD.…”
mentioning
confidence: 99%